Pharmacological targeting of the mitochondrial calcium-dependent potassium channel KCa3.1 triggers cell death and reduces tumor growth and metastasis in vivo - Magdalena Bachmann; Andrea Rossa; Tatiana Varanita; Bernard Fioretti; Lucia Biasutto; Stefan Milenkovic; Vanessa Checchetto; Roberta Peruzzo; Syed A. Ahmad; Sameer H. Patel; Robert Lukowski; Michael J. Edwards; et al. (Cell Death and Disease, 2022)
Abstract Ion channels are non-conventional, druggable oncological targets. The intermediate-conductance calcium-dependent potassium channel (KCa3.1) is highly expressed in the plasma membrane and in the inner mitochondrial membrane (mitoKCa3.1) of various cancer cell lines. The role mitoKCa3.1 plays in cancer cells is still undefined. Here we report the synthesis and characterization of two mitochondria-targeted novel derivatives of a high-affinity KCa3.1 antagonist, TRAM-34, which retain the ability to block channel activity. The effects of these drugs were tested in melanoma, pancreatic ductal adenocarcinoma and breast cancer lines, as well as in vivo in two orthotopic models. We show that the mitochondria-targeted TRAM-34 derivatives induce release of mitochondrial reactive oxygen species, rapid depolarization of the mitochondrial membrane, fragmentation of the mitochondrial network. They trigger cancer cell death with an EC50 in the µM range, depending on channel expression. In contrast, inhibition of the plasma membrane KCa3.1 by membrane-impermeant Maurotoxin is without effect, indicating a specific role of mitoKCa3.1 in determining cell fate. At sub-lethal concentrations, pharmacological targeting of mitoKCa3.1 significantly reduced cancer cell migration by enhancing production of mitochondrial reactive oxygen species and nuclear factor-κB (NF-κB) activation, and by downregulating expression of Bcl-2 Nineteen kD-Interacting Protein (BNIP-3) and of Rho GTPase CDC-42. This signaling cascade finally leads to cytoskeletal reorganization and impaired migration. Overexpression of BNIP-3 or pharmacological modulation of NF-κB and CDC-42 prevented the migration-reducing effect of mitoTRAM-34. In orthotopic models of melanoma and pancreatic ductal adenocarcinoma, the tumors at sacrifice were 60% smaller in treated versus untreated animals. Metastasis of melanoma cells to lymph nodes was also drastically reduced. No signs of toxicity were observed. In summary, our results identify mitochondrial KCa3.1 as an unexpected player in cancer cell migration and show that its pharmacological targeting is efficient against both tumor growth and metastatic spread in vivo.